Silver linings: will the COVID-19 pandemic instigate long overdue mental health support services for healthcare workers?. (June 2022) - Stephens, Tim; Vail, Emily A.; Billings, Jo
Summary: A study in this month's journal adds to the growing body of evidence regarding the potential mental health impacts on frontline healthcare staff working during the COVID-19 pandemic. As clinical academics representing critical care, nursing, and medicine, and a psychologist guiding support for frontline health and social workers, we offer our perspectives on this study. We discuss the balance between pragmatic and rigorous data collection on this topic and offer perspectives on the observed differential impact on nurses. Finally, we suggest that the pandemic might have a positive effect by instigating more robust mental health support services for National Health Service workers.